Beyond greenwashing: how circular economy metrics could revolutionize ESG investing - Munonye, Williams Chibueze; Munonye, Daniella Ifunanya (Frontiers in Sustainability, 2026)
Environmental, Social, and Governance (ESG) investing has gained global traction as a framework for sustainable finance, yet it remains vulnerable to greenwashing where firms exaggerate environmental claims to attract capital. This article argues that integrating circular economy (CE) metrics into ESG frameworks offers a more transparent and measurable approach to sustainability assessment. CE metrics such as Circular Material Use Rate (CMUR), lifecycle carbon intensity, and the Product Circularity Index (PCI) enable objective evaluations of material recovery, resource efficiency, and long-term ecological impact. Drawing on corporate examples like IKEA and Renault, and policy instruments such as the EU Circular Economy Action Plan and Digital Product Passports, the paper demonstrates how CE integration can reduce systemic risk and align financial performance with regenerative outcomes. Institutional entrepreneurship and regulatory innovations including Extended Producer Responsibility (EPR) and green public procurement are identified as key catalysts for mainstreaming circularity within ESG investing. Additionally, technologies like blockchain and AI-driven lifecycle analytics are highlighted as vital enablers of real-time verification and investor-grade circular data. Ultimately, this article envisions a transformative shift toward CE-aligned ESG investing, where financial decisions are grounded in auditable sustainability metrics and structured to promote long-term environmental integrity and accountability.